2023
DOI: 10.3390/ijerph20075255
|View full text |Cite
|
Sign up to set email alerts
|

The Switch to Online Learning during the COVID-19 Pandemic: The Interplay between Personality and Mental Health on University Students

Abstract: The switching from traditional to online learning during the COVID-19 pandemic was challenging for students, determining an increase in physical and mental health problems. The current paper applied a two-step cluster analysis in a large sample of n = 1028 university students (Mage = 21.10 years, SD = 2.45 years; range: 18–30 years; 78.4% females). Participants responded to an online survey exploring neuroticism, trait/state anxiety, general self-efficacy, academic motivation, fear of COVID-19, the impact of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 80 publications
0
0
0
Order By: Relevance
“…Interestingly, in line with previously cited studies on the Italian population [18][19][20][21][22][23], we found no changes in AD use comparable to young adults in other age groups, supporting the hypothesis that this subgroup of individuals had needed medication to treat their psychological distress during the lockdown periods and/or after the reopening phase. This evidence supports the association between younger age and lower levels of mental health during the COVID-19 pandemic [24][25][26][27][28][29][30][31][32][33][34][35][36]. We can also speculate that the increase in the use of ADs by young adults in the ASL TO4 Regione Piemonte may be related to prescriptions for the treatment of post-COVID-19 depression.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Interestingly, in line with previously cited studies on the Italian population [18][19][20][21][22][23], we found no changes in AD use comparable to young adults in other age groups, supporting the hypothesis that this subgroup of individuals had needed medication to treat their psychological distress during the lockdown periods and/or after the reopening phase. This evidence supports the association between younger age and lower levels of mental health during the COVID-19 pandemic [24][25][26][27][28][29][30][31][32][33][34][35][36]. We can also speculate that the increase in the use of ADs by young adults in the ASL TO4 Regione Piemonte may be related to prescriptions for the treatment of post-COVID-19 depression.…”
Section: Discussionsupporting
confidence: 80%
“…In this respect, the association between younger age and lower levels of mental health during the COVID-19 pandemic has been documented. In particular, young adults have been found to experience high rates of loneliness, anxious and depressive symptoms, stress, and sleep disturbances [24][25][26][27][28][29][30][31][32][33][34][35][36]. Whether these changes were associated with a parallel change in AD consumption needs to be better understood.…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown significant increases in distress among young people as a result of COVID-19 [16][17][18]. Transition to online learning for students and restrictions on routine daily activities affected the wellbeing of young people [19][20][21]. With access to in-person mental health support no longer possible, we examined whether the cost-effectiveness of recruitment differed between the lockdown and the post-lockdown period.…”
Section: The Vibe Up Trialmentioning
confidence: 99%